(A) REDUCED DENSITY MATRIX GENERATION ALGORITHMS IN SINGLE-PARTICLE-EXACT DENSITY FUNCTIONAL THEORY, (B) QUANTUM DYNAMICAL SIMULATION OF A TRANSVERSAL STERN-GERLACH INTERFEROMETER, (C) OPEN QUANTUM SYSTEM PROCESS TOMOGRAPHY - MIKOLAJ PARANIAK (2022)
Ph.D